NEW DIRECTION TO KNOWLEDGE AND TECHNOLOGY DRIVEN DEVELOPMENT ACCORDING FOR SOME EUROPEAN REGIONS - Nagy, Henrietta; Illés, Balázs; Káposzta, József (Journal of process management and new technologies, 2017)
The link between knowledge and wealth is considered as a proven fact in general and sometimes also on a regional level. Studies assume that services and products with higher added value have better profitability therefore they can create higher welfare for the producing company and finally to the region as well where it is located. We wanted to create a proper framework for clusters of knowledge intensive sectors and compare the specialization and concentration of the knowledge intenvise sectors in a European level to confirm, reject or modify these general assumptions. For that we used several approaches (purely regional, regional and sectoral, etc) and in this paper we would like to present our findings for the different sectors we investigated. Our reserach is based on Eurostat employment data, calculating regional location quotient from 1994 to 2008 and comparing these data with the GDP per capita values from the regions.